Link Capacity Dimensioning Model of ATS Ground Voice Network - Mrvelj, Štefica; Cvitković, Miro; Markežić, Ivan (Promet - Traffic&Transportation, 2012)
This paper considers the aspect of dynamic routing in a circuit switched network which is not a full connected network. It also presents the theoretical considerations that affect the selection and definition of routes as well as parameters that affect the link resource capacities. In restrictions set in this way imposed by ground/ground (G/G) voice communication in ATM (Air Traffic Management) the solutions of performance for the suggested dynamic routing scheme have been achieved.KEY WORDS: ATM, GG voice communication, dynamic routing, link capacity dimensioning